Systematic literature review: Implementation of ethnomodelling in mathematics learning - Muhammad Zia Alghar; Dwi Setiawati Radjak (Universitas Sarjanawiyata Tamansiswa, 2024)
There has been an increase in research on ethnomathematics in mathematics education, along with a rise in research on ethnomodelling. It triggers an increasing need and interest in how ethnomodelling is applied in mathematics learning. This study aims to review the literature on implementing ethnomodelling in mathematics learning. This research method is a systematic literature review with the PRISMA model. The research data are ethnomodelling-themed studies in mathematics learning published from 2019 to 2023 and obtained through the Google Scholar database. The articles obtained were 17 articles published in various countries. The results showed the implementation of ethnomodelling in mathematics learning, including different mathematical concepts, cultural objects, and ethnomodelling approaches. Also presented are contributions from various researchers and countries that have applied ethnomodelling in mathematics learning. The results of this study contribute to researchers, teachers, and practitioners in the form of a review of various ethnomodelling studies within the scope of mathematics concepts. So, they can be used as guidelines in developing culture-based mathematics learning strategies.